2016
DOI: 10.1007/s12039-016-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanocomposite of Chitosan-protected Platinum Nanoparticles Immobilized on Nickel Hydroxide: Facile Synthesis and Application as Glucose Electrochemical Sensor

Abstract: Novel nanocomposite of nickel hydroxide/chitosan/platinum was successfully synthesised with chitosan (CS) as a dispersing and protecting agent. Its potential application in non-enzymatic electrochemical glucose sensor was studied. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX) were used to characterize the composition and morphology of this nanocomposite. The electrochemical investigations of this glucose sensor exhibited remarkable ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the absence of glucose (blank), the Ni(OH) 2 /CS electrode exhibited a pair of well-defined redox peaks with the oxidation peak and reduction peak occurring at 0.50 and 0.30 V, respectively as is characteristic of a nickel based electrode. 32,37–39 These peaks can be assigned to the Ni( ii )/Ni( iii ) redox couple in alkaline medium and the reaction can be described as shown in eqn (1) and (2). In the presence of glucose, the valent NiOOH enables the oxidation of glucose to glucolactone as described in eqn (3).Ni + 2OH − → Ni(OH) 2 + 2e − Ni(OH) 2 + OH − ↔ NiOOH + H 2 O + e − NiOOH + glucose ↔ Ni(OH) 2 + glucolactone…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of glucose (blank), the Ni(OH) 2 /CS electrode exhibited a pair of well-defined redox peaks with the oxidation peak and reduction peak occurring at 0.50 and 0.30 V, respectively as is characteristic of a nickel based electrode. 32,37–39 These peaks can be assigned to the Ni( ii )/Ni( iii ) redox couple in alkaline medium and the reaction can be described as shown in eqn (1) and (2). In the presence of glucose, the valent NiOOH enables the oxidation of glucose to glucolactone as described in eqn (3).Ni + 2OH − → Ni(OH) 2 + 2e − Ni(OH) 2 + OH − ↔ NiOOH + H 2 O + e − NiOOH + glucose ↔ Ni(OH) 2 + glucolactone…”
Section: Resultsmentioning
confidence: 99%
“…Nickel hydroxide Ni(OH) 2 was prepared according to a previous reported procedure. 32 Briefly, 3.6 g of Ni(NO 3 ) 2 ·6H 2 O was dissolved in 25 mL of deionised water. 6 g of urea was added, and the solution was stirred for 1 h. The mix was transferred into a 25 mL Teflon-lined autoclave and was heated at 120 °C for 2 h. After which, the final products were centrifuged, washed several times with deionised water, and then dried in at 80 °C for 6 h. The obtained Ni(OH) 2 powder (20 mg) was added to 40 mL of ethanol–water (1 : 1, v/v ratio) solution and ultrasonicated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, platinum is also found to use in generating eco-friendly energy sources (Madsen et al 2011). Beside of all these, several reports have also highlighted that platinum is also beneficial for pharmaceutical industries as platinum has activity in producing bio-imaging, detecting biological molecules and modulating nanomedicine (Tanaka et al 2011;Moglianetti et al 2016;Rao et al 2016). Several physical and physio-chemical properties like, size, shape, surface structure and capping agent along with the dispersion state and stability help optimize and finally lead to formulate the desired PtNPs with specific target-based activity.…”
Section: Antimicrobial Effect Of Ptnpsmentioning
confidence: 99%
“…This result demonstrated that the CoPtNPs/Pt exhibits a better electrocatalytic activity attributed to its synergistic action since it has a high surface area and an excellent conductivity to promote the electron transfer between AA analyte and bulk-electrode surface. 38 The calibration plot for CoPtNPs/Pt electrode is given in Figure 8b. The response current for AA is linear on the concentrations range (10-500 µM) with a correlation coefficient (R 2 ) of 0.998.…”
Section: Amperometric Detection Of Aa On Coptnps/ptmentioning
confidence: 99%